Implementation Of Inlislite V. 3.2 System In Improving Service Quality At The Purworejo Regional Library - Analisatussobah, Analisatussobah; Faridah, Ida; Madum, Mohamad (JURNAL MANAJEMEN PENDIDIKAN, 2026)
This study aims to analyze the implementation of the INLISLite System in improving the quality of services at the Purworejo Regional Library. INLISLite is a library automation system developed to support the management of collections, circulation, and information services in an integrated and efficient manner. The research method used is a qualitative approach with descriptive research. Data collection techniques include observation, interviews, and documentation conducted with librarians and library users. The research results indicate that the implementation of INLISLite is able to improve the quality of library services, particularly in terms of the speed of circulation services, accuracy of collection data, ease of information retrieval, and the enhancement of librarian performance. Overall, the implementation of the INLISLite system makes a significant contribution to improving service quality at the Purworejo Regional Library and should continue to be developed through system optimization.